The Implication of The Supreme Courts Affirmation Towards Judex Facti Decision In a Final and Binding Judicial Award Which Still Providing a Chance to Perform Legal Action Through Arbitration After The Nullification of The Arbitration Award (International Journal of Psychosocial Rehabilitation, 2020)
The Arbitration Award is a binding adjudication precedent, but based on the provision of Article 70, Statute Number 30 of 1999 of Arbitration and Alternative Dispute Resolution (Statute of Arbitration), such award are admissible for nullification by the District Court and it is also a subject for an appeal to the Supreme Court of Indonesia. The verdict within the Supreme Court award Number 62 B/ Pdt. Sus-Arbt/ 2017 regarding the case of the nullification of Badan Arbitrase Nasional Indonesia’s award, has refused to discharge the authority of Badan Arbitrase Nasional Indonesia (BANI). The legal issues analyzed within this research are: Does the nullification of Arbitration Award resulting on nullification of Arbitration Clause? What are the implications of the affirming verdict of the Supreme Court’s award Number 62 B/Pdt. Sus-Arbt/2017 on Judex Facti’s award number 332/Pdt.G/Arb/2016/PN Jkt.Pst towards the dispute resolution process between the parties? The writing method applied to this thesis is a normative method with descriptive research, with the application of primary, secondary, and tertiary legal resources, analyzed in a qualitative manner. The nullification of Arbitration Award by the Supreme Court does not revoke the authorization of Arbitration and the implication of such awards is that the Pactum de Compromitendo is still enforceable and BANI is still the authorized choice of forum. The conclusions taken from the research conducted are: 1) The nullification of Arbitration Award resulting on nullification of the Arbitration Clause; 2) The implication of the Supreme Court’s award Number 62 B/Pdt.Sus-Arbt/2017 is that there is no certainty of law for the parties as a result of the binding and un-nullified enforceability of the arbitration clause based on the provision of the first paragraph of Article 1338, The Book of Indonesia Private Law. Recommendation: 1) PT. Republik Energi & Metal is advised to file for Judicial Review towards the case to the Supreme Court in order to annul the previous award of the Supreme Court; 2) The conflicting parties to establish Acte Compromis to nullify Arbitration Clause.